Opposing Actions of AKT (Protein Kinase B) Isoforms in Vascular Smooth Muscle Injury and Therapeutic Response. Issue 12 (December 2017) - Jin, Yu; Xie, Yi; Ostriker, Allison C.; Zhang, Xinbo; Liu, Renjing; Lee, Monica Y.; Leslie, Kristen L.; Tang, Waiho; Du, Jing; Lee, Seung Hee; Wang, Yingdi; Sessa, William C.; et al.
Abstract : Objective—: Drug-eluting stent delivery of mTORC1 (mechanistic target of rapamycin complex 1) inhibitors is highly effective in preventing intimal hyperplasia after coronary revascularization, but adverse effects limit their use for systemic vascular disease. Understanding the mechanism of action may lead to new treatment strategies. We have shown that rapamycin promotes vascular smooth muscle cell differentiation in an AKT2-dependent manner in vitro. Here, we investigate the roles of AKT (protein kinase B) isoforms in intimal hyperplasia. Approach and Results—: We found that germ-line–specific or smooth muscle–specific deletion of Akt2 resulted in more severe intimal hyperplasia compared with control mice after arterial denudation injury. Conversely, smooth muscle–specific Akt1 knockout prevented intimal hyperplasia, whereas germ-line Akt1 deletion caused severe thrombosis. Notably, rapamycin prevented intimal hyperplasia in wild-type mice but had no therapeutic benefit in Akt2 knockouts. We identified opposing roles for AKT1 and AKT2 isoforms in smooth muscle cell proliferation, migration, differentiation, and rapamycin response in vitro. Mechanistically, rapamycin induced MYOCD (myocardin) mRNA expression. This was mediated by AKT2 phosphorylation and nuclear exclusion of FOXO4 (forkhead box O4), inhibiting its binding to the MYOCD promoter. Conclusions—: Our data reveal opposing roles for AKT isoforms in smooth muscle cell remodeling. AKT2 is required for rapamycin's therapeutic inhibition of intimal hyperplasia, likely mediated in part through AKT2-specific regulation of MYOCD via FOXO4. Because AKT2 signaling is impaired in diabetes mellitus, this work has important implications for rapamycin therapy, particularly in diabetic patients. Abstract : Supplemental Digital Content is available in the text.